Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.5455/javar.2023.j648
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant bacteria in bovine milk in India

Abstract: Antibiotic resistance (ABR) is a global issue that draws the attention of all healthcare experts in the veterinary and medical fields. Of various factors, indiscriminate and unregulated antibiotic usage in the animals reared for food production, especially in cows and buffa¬loes suffering from mastitis, contribute significantly to the rising incidence of resistant bac¬teria. A literature survey reveals the spread of resistant strains of mastitis-causing bacteria, like Staphylococcus aureus and Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…While coagulase-positive S. aureus (CPS) is often the subject of research because it is the predominant isolate in bovine mastitis milk [43], CNS strains both belonging to the S. aureus species and other species of the Staphylococcus genus (generally considered non-pathogenic) are of less interest to researchers. These bacteria, generally considered non-pathogenic, constitute a reservoir and a vector for transferring antibiotic resistance genes to subsequent populations of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…While coagulase-positive S. aureus (CPS) is often the subject of research because it is the predominant isolate in bovine mastitis milk [43], CNS strains both belonging to the S. aureus species and other species of the Staphylococcus genus (generally considered non-pathogenic) are of less interest to researchers. These bacteria, generally considered non-pathogenic, constitute a reservoir and a vector for transferring antibiotic resistance genes to subsequent populations of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…There is a current emerging trend in the discovery of ARB and ARGs in milk, milk products, and dairy environments [ 105 ]. Many ARGs have also been found in bovine milk and the related environment and production facilities [ 106 ]. Different metagenomics tools have been used to study livestock and agricultural environments, and some of these studies have shown that the dairy environment has served as a source of ARGs in dairy products from dairy production plants [ 107 ].…”
Section: Antibiotic Resistance Genes and One Healthmentioning
confidence: 99%